“VIVE, MUERE, REPITE”: EL BLOCKBUSTER ANTE EL DESAFÍO INTERACTIVO - Antonio LORIGUILLO-LÓPEZ (Fonseca, Journal of Communication, 2023)
The appeal that interactive apps and games have been gathering has put in jeopardy the dominance of the film industry. The threat of interactivity has not only affected technical processes in film production, but their influence is felt in the storytelling devices of the flagship product par excellence of mainstream cinema: the action blockbuster.This paper proposes the analysis of the poetics of the contemporary action film that features certain traits of video game narratives by bringing up the case of Edge of Tomorrow (D. Liman, 2014). In particular, we focus in the construction of the time loop in which their characters are trapped, unable to escape death in the battlefield and forced to repeat the process ad nauseam.